2021
DOI: 10.1016/j.celrep.2021.109167
|View full text |Cite
|
Sign up to set email alerts
|

Mining HIV controllers for broad and functional antibodies to recognize and eliminate HIV-infected cells

Abstract: Highlights d Analysis of 185 HIV-envelope-specific antibodies from 15 spontaneous HIV controllers d Antibody downselection based on infected-cell recognition and Fc functionality d V3-loop-targeting antibodies were enriched among the top cell binders d Binding topology and Fc accessibility likely result in variable Fc functionality

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 97 publications
(120 reference statements)
1
6
0
Order By: Relevance
“…Fewer, or deletion of, PNGS in V1V2 suggested that the V3 loop may be selectively exposed and accessible on the cell surface. The slight fluctuation of genetic distance in the V3 region in our experiment confirmed that the conformational change of Env during virus assembly was inherently complex, as well as dynamic, on the cell surface ( Rossignol et al., 2021 ). The tetrapeptide of the V3 region is the binding site for the host to induce neutralizing antibodies and CTL reaction known to affect viral fusion and entry and determine the usage of co-receptors ( Bowder et al., 2018 ; Behrens et al., 2021 ).…”
Section: Discussionsupporting
confidence: 73%
“…Fewer, or deletion of, PNGS in V1V2 suggested that the V3 loop may be selectively exposed and accessible on the cell surface. The slight fluctuation of genetic distance in the V3 region in our experiment confirmed that the conformational change of Env during virus assembly was inherently complex, as well as dynamic, on the cell surface ( Rossignol et al., 2021 ). The tetrapeptide of the V3 region is the binding site for the host to induce neutralizing antibodies and CTL reaction known to affect viral fusion and entry and determine the usage of co-receptors ( Bowder et al., 2018 ; Behrens et al., 2021 ).…”
Section: Discussionsupporting
confidence: 73%
“…HIV is characterized by rapid evolution within and among infected individuals ( 26 ); which increases during chronic infection ( 27 29 ). This diversity presents a challenge for passive immunization strategies, as bNAbs targeting common Env epitopes would need to neutralize the transmitted/founder (TF) viruses for prophylaxis ( 5 , 30 ), as well as the variants that emerge in the face of immune pressure and antiretroviral therapy (ART) for therapeutic or cure applications ( 31 , 32 ). Considering the diverse bNAb biophysical properties and virus diversity, identification and characterization of the most suitable bNAbs for potential clinical use is a critical scientific goal.…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that several Fc-mediated mechanisms, including ADCC, antibody-dependent cellular phagocytosis (ADCP), antibody-dependent complement deposition (ADCD), aggregation and immune activation, participate in HIV inhibition (Figs. 1B, 2) [14,[33][34][35][36][37]. In addition, viruses can be directly opsonized by phagocytosis via Ab and FcR binding.…”
Section: Antibodies and The Pleiotropic Function Of The Humoral Respo...mentioning
confidence: 99%